Vertical distance from drainage drives floristic composition changes in an Amazonian rainforest - Schietti, Juliana; Emilio, Thaise; Rennó, Camilo Daleles; Drucker, Debora P.; Costa, Flávia Regina Capellotto; Nogueira, Anselmo; Baccaro, Fabricio Beggiato; Figueiredo, Fernando Oliveira Gouvêa; Castilho, Carolina Volkmer; Kinupp, Valdely Ferreira; Guillaumet, Jean Louis; Garcia, Ana Raquel M; et al. (Plant Ecology and Diversity, 2014)
Background: Plant composition changes with topography and edaphic gradients that correlate with soil-water and nutrient availability. Data on soil water for the Amazon Basin are scarce, limiting the possibility of distinguishing between soil and soil-water influences on plant composition. Aim: We tested a new proxy for water table depth, the terrain height above nearest drainage (HAND), as a predictor of composition in trees, lianas, palms, shrubs, and herbs and compared HAND to conventional measures of height above sea level (HASL) and horizontal distances from nearest drainage (HDND). Methods: Plant-species composition in 72 plots distributed across 64 km2 of lowland evergreen terra firme forest was summarised using non-metric multidimensional scaling (NMDS). NMDS scores were regressed against estimates of HAND, HASL and HDND. Results: Plant composition was highly correlated with the vertical distance from water table, capturing up to 82% of variation. All life forms showed highest turnover rates in the zone with seasonally water-saturated soils, which can extend 350 m from stream margins. Conclusions: Floristic composition is closely related to water table depth, and HAND appears to be the most robust available topographical metric of soil-water gradients. Brazilian conservation laws protecting 30-m-wide riparian buffers are likely to be too narrow to encompass the full zone of highest floristic turnover and may be ineffective in safeguarding riparian plant diversity. © 2014 Copyright 2013 Botanical Society of Scotland and Taylor & Francis.